CHARACTERISTICS AND CHANGES IN PATTERNS OF SETTLEMENT FISHERMEN KARANG PANAS ENVIRONMENT, SOUTH AMPENAN MATARAM CITY - Wardi, Liza Hani Saroya; Rahmawati Sushanti, Ima; Widayanti, Baiq Harly (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
The purpose of this study is to look at the characteristics of the fishing settlement patterns formed in the Karang Panas before and after relocation, and identify the factors that influence what changes occur in the new fishing settlement. This study uses a qualitative method with rationalistic approach. The data collection was done by field observations by directly collecting data in the field and interviews are useful to obtain additional information that can complement and support the data obtained from field observations. The results ofÂ this study are the characteristics of the fishing settlement patterns in the environment before it relocated Karang Panas linear shape, face to face follow Ampenan shoreline. Those that shaped spread pattern while forming a linear pattern oriented toward the coast . In the new settlement the two sides are patterned parallel gradial. This pattern was deliberately drafted by the City of Mataram for residential land mengefesiensi reef fishing hot new environment and facilitate accessibility between residential one another. Disadvantages of this pattern is the absence of a common room which comes as naturally as shared space repair fishing nets and drying chamber as a means of socialization in the morning and afternoon. Togetherness which is the hallmark of the previous settlement patterns do not appear in the new settlements. While the factors that affect settlement patterns of changes in the characteristics of the fishing environment Karang Panas namely : 1) internal factors (endogeen), which is caused by the desire of the people want to relocate themselves in order to avoid the danger of seawater abrasion and personal social movement of the public to hold changes based on life choices adjust the times, 2) external factors (exogeen), which is the policy of the City of Mataram on relocation settlements and encouragement of the development environment that supports the demands of the times of economic activity